DNA barcoding to resolve the confusion in identifying Tribolium confusum and Tribolium castaneum - Md Aslam, Abu Faiz; Sultana, Sharmin; Das, Sumita Rani; Howlader, Abdul Jabber (Bangladesh Journal of Zoology, 2019)
Tribolium confusum and Tribolium castaneum (Coleoptera: Tenebrionidae) are two very confusing pest species while identification is done on the basis of morphology only. Such pests are discovered in stored grain as immature stages, which further complicates the identification process. Accurate identification of these pests is urgently required for integrated pest management. In this research, DNA barcoding was used to identify these pests accurately at any life stage. A 658 bp fragment of the mitochondrial cytochrome c oxidase subunit I (COI) gene was analyzed. DNA barcode dataset of T. confusum (GeneBank Acc. no. MK120453.1) and T. castaneum (Acc. no. MK411585.1) were constructed. The nucleotide composition reveals that average AT contents (59.9%) were higher than the GC contents (38.6%). Phylogenetic analysis by maximum likelihood method showed that both the species were originated from a common major clade. About 17.13% nucleotide differences were noted between the CO1 sequences by multiple sequence alignment. The interspecies nucleotide genetic distance (0.200) was calculated using Kimura 2 parameter. Haplotype analysis showed high genetic diversity (112 mutaional steps) among them. Bangladesh J. Zool. 47(2): 333-342, 2019